Β-Alanine under pressure: towards understanding the nature of phase transitions1. Issue 10 (14th March 2015) - Zakharov, Boris A.; Tumanov, Nikolay A.; Boldyreva, Elena V.
<x xml:space="preserve">Abstract</x> We report the unusual behavior of β-alanine under pressure.